Optimalisasi Penggunaan Platform Digital Aktivitas Literasi Berbasis Science, Tecnology, Engeneering, Art, Math (STEAM) Untuk Guru Sekolah Dasar - Susanto, Edi; Asyari, Ahmad; Kurniawati, Ike (Forum Kerjasama Pendidikan Tinggi, 2025)
Implementing the independent curriculum at the elementary school level requires an emphasis on students' thinking skills. Learning is not merely the transfer of knowledge through textbooks, but needs to be designed through activities carried out directly by students. One such activity is through activities to strengthen the Pancasila profile, which are carried out to support student skills. However, the problem is that the activities designed by teachers tend to be entrepreneurial, but still lack a focus on literacy activities that support students' thinking skills. This activity aims to improve teachers' abilities in designing literacy activities and using digital platforms for literacy activities based on Science, Technology, Engineering, Art, and Mathematics (STEAM) in elementary school learning. Partners in this community service activity are elementary school teachers who are members of the KKG GTK Kombel 7, Tebat Karai District, Kepahiang. The target for this activity is 100 teachers and 25 elementary school students. The method of implementation of this activity is through training. The stages of this activity consist of: 1) preparation stage (coordination and socialization, design of STEAM-based literacy activities, and digital platform design), 2) implementation stage (platform use and implementation in class), and 3) evaluation and monitoring stage. The results of this activity are: 1) there was an increase in participants' ability to design STEAM-based literacy activities (score 55 on the pretest and 85 on the posttest), and 2) an increase in participants' ability to use the digital platform for STEAM-based literacy activities, with an average score of 90. In addition, students' responses in learning using literacy activities were, on average, in the high category. As a suggestion, teachers can design literacy activities in various materials for each learning area by integrating surrounding manipulative objects into a digital platform.